Self-rated Attractiveness and Sociosexual Behavior Predict Gay Men's Preferences for Masculine Cues in Male Voices in China. (7th May 2019) - Zhang, Jing; Zheng, Lijun; Zheng, Yong
Theory and some evidence suggest that masculine characteristics (e.g., lower pitched voice) will predict indices of men's long-term health. In a related finding, researchers have demonstrated that the attractiveness of individuals predicts variation in their mate preferences. As self-perceived attractiveness may predict sociosexuality (i.e., the willingness of individuals to engage in restricted or unrestricted sexual relationships), we investigated how self-rated attractiveness and sociosexuality influence preferences regarding male voices among 338 gay men across different cities in China. Each participant was randomly presented with six pairs of male voices and gave preferences using a forced-choice method; each pair of male voices consisted of a masculine (lower pitched) and feminine (higher pitched) version of the same original voice. Our findings suggested that gay men who perceived themselves as more attractive showed stronger preference for lower pitched voices compared with self-perceived less attractive individuals. In addition, we found that gay men's sociosexuality score was positively correlated with their preference for masculine cues in male voices, indicating that gay men who were less sociosexually restricted preferred lower pitched voices over higher pitched versions compared with men who were more restricted. Our study presents evidence contributing to a better understanding of condition-dependent strategies of partner choice in gay men.